تحسين أداء خدمة الإرسال الراديوي العام المحزم ) (GPRS في شبكة الاتصالات الخليوية السورية - حسن عباس; تاج الدين جركس; جهاد نجد (Tishreen University, 2019)
نظراً للاستخدام الهائل للانترنت والاتصالات اللاسلكية, فقد تم تطوير تقنية جديدة تمكن من استخدام الانترنت بواسطة الطرفيات اللاسلكية. تعتبر خدمة الإرسال الراديوي المحزم العامة( General Packed Radio Service , GPRS) معياراً جديداً يقدم خدمات النقل بالرزم عبر شبكة GSM التقليدية بطريقة أكثر فعالية و موثوقية. الشبكة المنفذة للـ GPRS هي خطوة لاحقة لشبكة GSM تقوم بتقديم خدمات وتطبيقات جديدة، ويعتبر التقييم والمقارنة بين التطبيقات والخدمات بشكل مستقل أمراً ضرورياً للوصول إلى هذه الغاية. في هذا البحث كانت منصة الاختبار هي الشبكة السورية الخليوية نفسها أداة للاختبار بالزمن الحقيقي من أجل تقدير أداء GPRS . وقد تم التركيز على التدفق كتابع لنسبة الإشارة الحاملة إلى التداخل (C/I) من أجل تطبيقين أساسيين هما: عملية نقل ملف و إنشاء قناة Streaming، بالإضافة إلى بارامترات أخرى تم تقديرها هي BER ,FER ,RTT, كما تم تقدير الأداء خلال عملية إعادة اختيار الخلية، و دراسة هذه التطبيقات في بيئات انتشار مختلفة. بينت الدراسة أن التطبيق UDP المختبر هو تقريباً أكبر بـ 2dB من التطبيق TCP عند نفس الظروف. أخيراً من أجل حساب التدفق تم تقدير بارامترات إضافية هي عدد قنوات PDCH في الخلية وعدد مستثمري GPRS في الخلية وصنف الفجوات المتعددة والمعدل البتي للتطبيق. Due to the explosive use of Internet and wireless communication, new techniques for introducing Internet on wireless terminals have been developed. The General Packed Radio Service (GPRS) is a new standard providing packet data services over the traditional GSM network in a more efficient and reliable way. With the GPRS network implemented, the next step for GSM is to provide new services and applications. Evaluation and comparison between individual services and applications are then indispensable assets in order to reach this goal. In this paper, a test bench is Syriatell Network itself as a real time test tool for GPRS performance evaluation. The focus has been on throughput as function of the carrier to interferer ratio (C/I) for two basic applications: file transfer and streaming. Additional parameters that have been assessed are BER, FER, RTT and performance during cell reselection. The performance of these applications has also been studied for different propagation environments. The study has shown that the tested UDP application is approx. 2 dB more robust than the TCP application under similar conditions. Additional parameters that have been assessed are a number of available PDCH per cell, number of active users per cell, multislot class and application bit rate per user, for finding estimated throughput.